COMOVEMENT AND VOLATILITY ANALYSIS USING THE WAVELET COHERENCE METHOD (CASE STUDY OF WORLD OIL, GOLD, AND RUPIAH EXCHANGE RATE PRICES FOR LQ45 STOCK PRICE INDEX) - Ahsanah, Adilah
Physics is a science discipline that works according to scientific methods. The scientific method only accepts reason, logic, and experimental evidence between something real scientifically or not. In practice, physics scientists have recently been modeling complex systems using these scientific methods. This model is used to find out the dynamics of a system that fluctuates and is influenced by various other elements. One of the models studied is modeling on financial markets which are part of econophysics. Econophysics is a science field that explains economic concepts using theoretical approaches and physical methods. In this study, the dynamics in the financial markets studied are comovement and volatility between commodities and the rupiah exchange rate with the closing price of the LQ45 stocks index for the period of January 2015 – April 2020. The method used in this study is Wavelet Coherence (WTC). This method can change or decompose the time series that are reviewed into a time and frequency domain simultaneously. The mother wavelet form used is Morlet. A program used to process the data has been developed by Grinsted using MATLAB. This method can generate a Wavelet Power Spectrum (WPS) and Wavelet Coherence (WTC) analysis to illustrate the areas in time with high volatility and comovement. Volatility analysis with WPS shows that gold prices have the lowest volatility and stock prices have the highest volatility. Then the Wavelet Coherence (WTC) analysis shows the highest and lowest comovement between stock prices against oil prices, gold prices, and the rupiah exchange rate respectively occurred in UNVR and SMGR, UNVR and PTPP, and SMGR and PTBA stocks. Also, an investment strategy analysis is conducted based on the type of investor that consist of aggressive, moderate, and conservative investors who invest in stocks with high, medium, and low comovement and the current economic turmoil.